Pembiayaan Ramah Lingkungan : Studi Di Bank BRI Syariah Kawi Malang - ermawati ermawati (Journal of Islamic Business Law, 2018)
This study aims to find out the efforts of BRI Syariah Kawi Malang bank in providing eco-friendly financing and the efforts of this institution according to structural functionalism theory Talcott Parsons. This research type is empirical juridical research with law anthropology approach by descriptive result from main data that is interview and document study and supported by secondary data to answer problem formulation. While the stage of data processing done in this research is editing that is checking back data from the tape recorder, classifying the grouping of data that has been obtained in accordance with the formulation of the problem, verifying is checking the data back to the informant, analyzing the results and linked to the theory applicable, And concluding is to conclude the results of data that has been processed. The results of this study are summarized as follows: (1) BRI Syariah bank's effort is to issue a policy must have a business interruption permit or guarantee that directly impact on the environment, this license is verified in the relevant offices. (2) based on the analysis of the theory of functionalism, the institute is in synergy with other institutions.